what is 6 to the power of -6 x 6 to the power of 2

1 answer

To solve the expression \(6^{-6} \times 6^{2}\), we can use the properties of exponents.

When multiplying two expressions with the same base, we can add their exponents:

\[ 6^{-6} \times 6^{2} = 6^{-6 + 2} = 6^{-4} \]

Now, writing \(6^{-4}\) in positive exponent form gives us:

\[ 6^{-4} = \frac{1}{6^{4}} \]

Finally, \(6^{4}\) can be calculated as:

\[ 6^{4} = 6 \times 6 \times 6 \times 6 = 1296 \]

Thus,

\[ 6^{-4} = \frac{1}{1296} \]

The final answer is:

\[ \frac{1}{1296} \]